COVID-19 seroprevalence in primary and secondary healthcare workers (HCWs) - Murphy, Gregory P.; Garry, Catherine; Van Baarsel, Susan; Coleman, Tina; Shovlin, Ben; Fogarty, Ciara; Williams, Conor; Lang, Patricia; Casey, Caroline; Leonard, Lenora; Ovryakh, Natalia; Murphy, Philip G.; et al. (International Journal of Infection Control, 2021)
Professional anxiety existed early in the coronavirus disease 2019 (COVID-19) pandemic with challenging infection prevention and control support. The aims of this study were to compare epidemiological features of healthcare workers (HCWs) within primary and secondary care with their serological evidence of infection. A prospective observational cohort of 1,916 HCWs completed a questionnaire, and their sera were assayed for detectable antibody to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleoprotein in the first wave of the pandemic. Datasets were compared between the two sub-cohorts in primary and secondary care and between the combined seropositive and seronegative cohorts. Curiosity of antibody status was high. Detectable antibody was 7% in the primary care and 5% in the secondary care workers at a time of 1.7% in the general community. Inappropriate personal protective equipment (PPE) was more common in primary care, and detectable antibody was twice as prevalent in HCWs who felt they did not have appropriate PPE. Contact tracing was perceived to be inadequate although it was more commonly performed in the seropositive cohort suggesting appropriate prioritisation. Both temperature and symptom checking alerts and work exclusion were significantly more prevalent in the seropositive cohort. The seroprevalence data support increased risk for HCWs, the importance of appropriate PPE and the usefulness of the daily temperature and symptom checks, particularly in primary care.